Regio- and stereoselective synthesis of beta-amino alcohols over titanosilicate molecular sieves - Satyarthi, Jitendra K.; Saikia, Lakshi; Srinivas, Darbha; Ratnasamy, P. (Applied Catalysis A-General, 2007)
A novel application of titanosilicate molecular sieves in the synthesis of P-amino alcohols via aminolysis of epoxides, at mild and solvent-free conditions, is reported, for the first time. A range of beta-amino alcohols with nearly 100% regio- and stereoselectivity was produced over these reusable solid catalysts in high yields. (C) 2007 Elsevier B.V. All rights reserved.
Keywords: Aminolysis of epoxides; synthesis of beta-amino alcohols; Ti-MCM-41; titanosilicate molecular sieves

Regiospecific oxyhalogenation of aromatics over SBA-15-supported nanoparticle group IV-VI metal oxides - Saikia, Lakshi; Rajesh, M.; Srinivas, Darbha; Ratnasamy, P. (Catalysis Letters, 2010)
TiO(x), VO(x), MoO(x) and WO(x) supported on SBA-15 exhibit efficient catalytic activity for oxyhalogenation of aromatics with the H(2)O(2)-halide ion system. Unlike the hitherto known solid catalysts, these reusable catalysts yield the para-halogenated product with 100% selectivity at 298 K and moderate acidic pH (3-5). The catalytic activity was enhanced by five orders of magnitude when supported on SBA-15.
Keywords: Haloperoxidase activity; Ordered mesoporous silica; Oxyhalogenation of aromatics; SBA-15; Supported metal oxides